Green Accounting dalam Ekosistem Media Digital: Strategi Komunikasi Transparansi dan Penguatan Reputasi Berbasis Sustainable Development Goals (SDGs) - Irfan Sophan; Bella Nur Fatia Dewi; Andri Indrawan; Nurhidayah binti Shamsudin (Communicatus: Jurnal Ilmu komunikasi, 2026)
The growing global awareness of environmental issues has encouraged corporations to adopt green accounting practices as a mechanism for ecological accountability. In the digital era, however, environmental accounting is no longer limited to internal reporting activities but has evolved into a strategic instrument of public communication. This study aims to examine how green accounting information is transformed through digital media into value-based communication that shapes stakeholder trust, corporate reputation, and long-term sustainability advantage. Using a qualitative descriptive approach, this research relies on interpretive literature review and document analysis of sustainability reports, corporate digital publications, and global policy frameworks related to the Sustainable Development Goals (SDGs). The analysis focuses on how environmental data are disclosed, narrated, and socially constructed within digital spaces. The findings reveal that digital platforms expand the audience of accounting information, creating greater visibility and continuous public scrutiny. Numerical disclosures become influential only when translated into meaningful narratives that resonate with ethical commitments and global sustainability standards. The alignment between measured performance, authentic communication, and SDGs contributes significantly to the development of stakeholder trust. Trust, in turn, accumulates into corporate reputation, which functions as a critical intangible asset in competitive environments. This study contributes to the literature by integrating accounting, digital communication, and sustainability into a unified conceptual framework. It positions green accounting not merely as a reporting obligation but as a social process through which legitimacy is negotiated in the public sphere. The research highlights that the future of corporate sustainability depends on the organization’s capacity to manage the interconnection between data credibility, technological transparency, and societal expectations. Keywords: green accounting, digital disclosure, stakeholder trust, corporate reputation, SDGs.